Predicters of individual psychotic experiences after trauma: a series of longitudinal studies - Geddes, G (2018)
Environmental risk factors including trauma have been linked with individual positive psychotic experiences. The mechanisms underlying these relationships are not well understood. This thesis investigates longitudinally the occurrence of different reactions - paranoia, grandiosity, hallucinations and PTSD - in the direct aftermath of interpersonal trauma. It attempts to ascertain how distinguishable these different experiences are from each other, and the shared and differential factors that lead to their persistence. Chapter 1 sets out the argument of the thesis, and it includes a systematic review of empirical studies investigating mechanisms underlying the relationship between trauma and individual psychotic experiences. The review identifies the absence of longitudinal research on grandiosity, and therefore Chapter 2 reports the first longitudinal, developmental test of grandiosity (N = 4997). Endorsement of grandiose beliefs in adolescence was found to be predicted by overestimation of own success, peer victimisation and perceived harsh parental discipline as assessed in childhood. Chapter 3 reports the first longitudinal study of processing of a recent trauma on the occurrence of hallucinations. A secondary analysis of a previous study that focussed on paranoia and PTSD in the aftermath of an assault (N=106) finds that problematic peri-traumatic processing, cognitive response styles, and negative post traumatic appraisals were predictive of later occurrence of hallucinations Informed by this and previous chapters the main empirical study was set up to provide a description of the occurrence of paranoia, grandiosity, hallucinations and PTSD in the days and months following an interpersonal assault, to assess how distinguishable these different outcomes are and to test the ability of theory derived variables to predict their persistence. The study recruited 95 assault survivors following their attendance at Accident and Emergency Department for injuries sustained in the assault. Participants were assessed 10 days post assault and followed up over the next 6 months. Whilst differential prediction for grandiosity was identified, paranoia, hallucinations and PTSD were predicted by a very similar pattern of variables. Chapter 7 takes up the contentious issue of sleep in the direct aftermath of trauma and its role in the occurrence of intrusions and PTSD. While sleep has been shown to play a causal role in the development of paranoia and hallucination, there remain two opposing views about the role that sleep plays in the development of PTSD. The sleep of 25 assault survivors was measured on the first night post-assault and over the following week. Lower sleep duration, efficiency and quality were predictive of later paranoia, hallucinations and PTSD. Overall this thesis demonstrates that a range of adverse reactions are not uncommon in the immediate aftermath of trauma and that cognitive processing found to explain PTSD appears also to explain the occurrence of paranoia and hallucinations. Except for grandiosity, differential prediction between PTSD, paranoia, and hallucinations is hard to find empirically. Longitudinal studies cannot prove causation and what is needed going forward are intervention studies that target identified, putative causal processes.